Transformasi Digital Pemasaran Produk Herbal UMKM KYTA Melalui Pelatihan Dan Pendampingan Pembuatan Katalog Digital - Muhammad Roestian Fahmi Nasution; Nora Anisa Br Sinulingga; Binsar Sihombing; Sofian Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
Although MSMEs are an essential part of the national economy, many still face challenges in utilizing digital technology to enhance their business competitiveness. As a micro-enterprise based in Medan City, KYTA MSME produces herbal beverages made from natural ingredients. They encounter difficulties in digital marketing, particularly in showcasing their products and disseminating information online. The objective of this community service activity is to enhance the capacity of KYTA MSME through training and mentoring in the creation of digital catalogs, which serve as effective and contemporary promotional tools. The results of the activity indicate that the MSME actors gained a better understanding of digital technology, basic graphic design skills, and knowledge of visual marketing strategies. The outputs of the activity include ready-to-use digital catalogs, instructional modules on using Canva and Google Drive, and documentation of the reporting process. It is expected that this program can serve as a replicable model for the digitalization of other MSMEs and encourage more flexible marketing transformation in the digital economy era.